Interactive effects of fluoride and seleno-l-methionine at environmental related concentrations on zebrafish (Danio rerio) liver via the gut-liver axis. Issue 127 (August 2022) - Zhang, Xiulin; Chen, Jianjie; Wang, Guodong; Chen, Hongxing; Cao, Jinling; Xie, Lingtian; Luo, Yongju
Abstract: Fluoride (F) is a ubiquitous aquatic environmental pollutant and co-exists with other pollutants to form combined pollution. Selenium (Se) is beneficial at low levels yet toxic at high levels and can interact with some metals. However, the interactive effects of F and Se on the liver in fish remains enigmatic. In this study, zebrafish ( Danio rerio ) were exposed to F (80 mg/L) and dietary seleno-l -methionine (Se-Met, 0.25, 0.5 and 1.0 μg/g dry weight) alone or in combination for 90 d. The results indicated that co-treatment to F and Se-Met attenuated the histopathological damage, oxidative stress, and inflammatory in the liver, compared with the F treatment alone. Meanwhile, dietary Se-Met treatment improved F-induced intestinal barrier dysfunction, increased the transcripts of tight junction proteins ( ZO-1, Claudin-1 and Occludin ), and restored the homeostasis of intestinal microbiota. Moreover, dietary Se-Met ameliorated F-induced intestinal and liver inflammation by inhibiting lipopolysaccharide (LPS) levels and transcripts of TLR4 and p65 in the intestine and liver. This study manifested that Se-Met alleviates F-induced liver and intestinal injury when both co-occur at specific concentrations, and that the gut-liver axis pathway may serve as a mechanistic base for these alleviative effects. Graphical abstract: Image 1 Highlights: Interactive effects of F and dietary Se-Met was studied in Danio rerio. Co-treatment to Se-Met alleviates F-induced liver damage. Co-treatment to Se-Met attenuates F-induced intestinal barrier damage. Co-treatment to Se-Met and F modulates intestinal microbiota. The gut-liver axis may serve as a mechanism of Se-Met alleviating F toxicity.